The Effect Of Work Stress And Work Discipline On Employee Performance With Work Motivation As An Intervening Variable At Pt Hki Jakarta - Yusuf Kibar; Kiki Farida Ferine; M. Isa Indrawan (Yayasan Multidimensi Kreatif, 2023)
This study aims to determine the effect of Work Stress and Work Discipline on Employee Performance with Work Motivation as an Intervening Variable at PT HKI Jakarta. This research is an explanatory research with a quantitative approach, and the methods used in this study are observation, questionnaires, interviews, and literature studies. The population in this study is a homogeneous limited population, namely PT HKI Jakarta employees as many as 68 permanent employees. The technique used in sampling using saturated sampling, so that the number of samples is 68 respondents. The data analysis technique is SEM (Structural Equation Modeling) using the Smartpls program.4. The results showed that work discipline did not have a significant influence on employee performance variables. Work discipline has a significant influence on work motivation variables. Work motivation has a significant influence on employee performance variables. Work stress has a significant influence on employee performance variables. Work stress has a significant influence on work motivation variables. Work discipline indirectly through work motivation as an intervening variable has a significant effect on the performance of PT HKI Jakarta employees. Work stress indirectly through work motivation as an intervening variable has a significant effect on the performance of PT HKI Jakarta employees.